2018
DOI: 10.5606/archrheumatol.2018.6336
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effects of Leukocyte-Rich and Leukocyte-Poor Platelet-Rich Plasma on Pain and Functionality in Patients With Lateral Epicondylitis

Abstract: According to our study findings, lateral epicondylitis does not seem to affected either leukocyte-rich-PRP or leukocyte-poor-PRP on pain and function in the short term. Leukocyte concentration had no association with post-injection local inflammatory reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…Hanish et al did not find any significant differences between leukocyte-poor (LP)-PRP and LR-PRP in treatment of Achilles tendinopathy in VISA-A and VAS [103]. Further, Yerlikali et al showed no significant differences in pain, functional parameters, and inflammatory reaction between LR-PRP and LP-PRP in patients with lateral epicondylitis [104]. Riboh et al performed a meta-analysis including six RCTs and three prospective comparative studies comparing efficacy of leukocyte concentration in OA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hanish et al did not find any significant differences between leukocyte-poor (LP)-PRP and LR-PRP in treatment of Achilles tendinopathy in VISA-A and VAS [103]. Further, Yerlikali et al showed no significant differences in pain, functional parameters, and inflammatory reaction between LR-PRP and LP-PRP in patients with lateral epicondylitis [104]. Riboh et al performed a meta-analysis including six RCTs and three prospective comparative studies comparing efficacy of leukocyte concentration in OA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hilber et al [50] reported that leukocyte-reduced PRP stimulates the proliferation of tenocytes and Zhang et al [51] demonstrated that proliferation of tendon stem cells cultured in leukocyte-rich was significantly decreased and tendon stem cells cultured in leukocyte-poor PRP produced more collagen and formed tendon-like tissue. However, these were in vitro studies and clinical studies did not show any significant difference between leukocyte-rich and leukocyte-poor PRPs [53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesised that these side effects are caused by the catabolic potential induced by the interleukin-1β (IL-1β) and the tumour necrosis factor-α, and their subsequent stimulatory effects on the nuclear factor κB signalling pathway. Furthermore, it is theorised that high concentrations of leucocytes in PRP may intensify MMP expressions and therefore cause excessive degradation of the extracellular matrix tissue and thus inhibit healing [5,33,34]. Conversely, though, tissue regeneration is equally reliant on the interactions and cross-talk between surrounding cells and leucocytes.…”
Section: Leucocytes: Lr-prp and Lp-prpmentioning
confidence: 99%